Experimental determination of the quantity and distribution of chemical crosslinks in unaged and aged natural rubber, part 1: Peroxide vulcanization. (September 2018) - Howse, Samantha; Porter, Christopher; Mengistu, Tesfaldet; Pazur, Richard J.
Abstract: A set of unfilled and stabilized natural rubber compounds containing different dicumyl peroxide concentrations were prepared and their chemical crosslink densities were determined using a variety of experimental techniques: stress–strain (Mooney-Rivlin), equilibrium solvent swell (Flory-Rhener) and low field time domain Nuclear Magnetic Resonance (NMR) by the Double Quantum (DQ) method. Testing was carried out on both the unaged and heat aged (96 h at 80 °C) samples. Increasing peroxide level caused a corresponding rise of crosslink density and a decrease in the chain entanglement density, while the relative crosslink distribution width remained unchanged. The molecular weight between entanglement points was in the expected range for natural rubber. Heterogeneous areas of high crosslinking (clusters) were low in concentration. Heat aging caused properties to deteriorate due to chain scission reactions that eliminated network chains creating a more heterogeneous system. Defect levels increased and more toluene soluble uncrosslinked chains were detected. The network chain and chain entanglement densities decreased with heat aging and the molar mass distribution between crosslinks substantially broadened independent of peroxide loading. Highlights: The crosslink density increased while the chain entanglement density decreased with peroxide loading. The relative distribution of the molar mass between crosslinks did not change with peroxide level. Heterogeneous areas of high crosslinking (clusters) were generally low in concentration. Crosslink and chain entanglement densities decreased at each peroxide level upon heat aging. The molar mass distribution between crosslinks substantially broadened due to heat aging.